2002
DOI: 10.1200/jco.2002.01.133
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of the Proteasome Inhibitor PS-341 in Patients With Refractory Hematologic Malignancies

Abstract: PS-341 was well tolerated at 1.04 mg/m(2) on this dose-intensive schedule, although patients need to be monitored for electrolyte abnormalities and late toxicities. Additional studies are indicated to determine whether incorporation of dose/body surface area yields a superior PD model to dosing without normalization. PS-341 showed activity against refractory multiple myeloma and possibly non-Hodgkin's lymphoma in this study, and merits further investigation in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
428
3
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 699 publications
(460 citation statements)
references
References 18 publications
19
428
3
10
Order By: Relevance
“…Inhibition levels were also equivalent in patients with MM receiving 20 mg/m 2 carfilzomib as a 2‐ to 10‐min or 30‐min infusion, which is consistent with results reported in animals (Yang et al , 2011). It is noteworthy that the overall level of CT‐L inhibition seen with carfilzomib is higher than the 65–70% inhibition rate reported in bortezomib‐treated patients (Orlowski et al , 2002; Papandreou et al , 2004; Moreau et al , 2008). Using ProCISE, we also demonstrated that the administration of carfilzomib inhibits proteasome subunit occupancy in bone marrow–derived tumour cells.…”
Section: Discussionmentioning
confidence: 79%
“…Inhibition levels were also equivalent in patients with MM receiving 20 mg/m 2 carfilzomib as a 2‐ to 10‐min or 30‐min infusion, which is consistent with results reported in animals (Yang et al , 2011). It is noteworthy that the overall level of CT‐L inhibition seen with carfilzomib is higher than the 65–70% inhibition rate reported in bortezomib‐treated patients (Orlowski et al , 2002; Papandreou et al , 2004; Moreau et al , 2008). Using ProCISE, we also demonstrated that the administration of carfilzomib inhibits proteasome subunit occupancy in bone marrow–derived tumour cells.…”
Section: Discussionmentioning
confidence: 79%
“…Another example of this type of approach may prove to be the use of the proteasome inhibitor bortezomib (VELCADE ® ), or a bortezomib-based regimen, in patients with deletions of chromosome 13. Originally, this agent was found to have activity against relapsed/refractory multiple myeloma in the phase I-III settings [18][19][20] and, interestingly, subset analysis of the phase II study 19 showed that patients with deletion (del) of 13 had the same response rate as controls. When results of the phase III trial 20 were analyzed in this regard, it was found that patients with del 13 who received dexamethasone had an inferior survival compared with matched controls, as would be expected.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Following encouraging preliminary phase I clinical trial results [5], 202 patients (193 evaluable for response) with relapsed or refractory MM were treated in the pivotal phase II SUMMIT trial [6] with bortezomib (1.3 mg/m 2 i.v.) on days 1, 4, 8, and 11 of a 21-day cycle for a maximum of eight cycles.…”
Section: Efficacy and Safety Of Bortezomibmentioning
confidence: 99%